Первые сведения о миксоспоридиях рыб открытых вод юго-восточной части Тихого океана - Ковалева, А.А.; Гаевская, А.В. (Вестник зоологии, 1983)
Six species of Mixosporidia are found in fishes of the South-East Pacific Ocean open waters; five of them are described as new: Ceratomyxa meglitschi sp. 1 C. pacifica sp. n., Leptotheca ovale sp. n., Pseudalataspora scombri gen. et sp. n., Kud: caudata. A new genus Pseudalataspora gen. n. differs from closely related Alataspo by spore alate projections structure: they are bifid, joined over their anterior margi Faunal peculiarities of the studied area are analyzed.